Toxicological assessments of aqueous extracts from seaweeds Bryothamnion triquetrum (Gmelin) M.A.Howe in vitro and models animal studies - Vidal-Novoa, A; Fallarero-Linares, A; Labañino, M; Sánchez-Lamar, A; Batista-Gonzalez, AE; Silva, AMO; Mancini-Filho, J (Ars Pharmaceutica (Internet), 2012)
Aim: The aim of this work was to evaluate the toxicity of an aqueous extract from seaweed Bryothamnion triquetrum. Materials and Methods: Ames assay was developed with S. typhimurium TA 1535, TA 1537 and TA 1538 with and without metabolic activation. Citotoxicity study was carried out with intestinal cells Caco-2 during 24 and 48 hours of exhibition to the extract and the viability was evaluated with the technique of Propidium iodide. Acute Toxicity was carried out with mice Balc/c males for via oral and intraperitoneal and the Toxicity for Repeated Dose was developed with rats Wistar of both sexes, during 3 months for via oral with dose of 8 and 32 mg/kg. Results: Results of Ames assays showed that this extract is not direct mutagen or promutagen in quantity until 1000 μg. The cytotoxic effect (LC50) of Caco-2 cells after 24 and 48 h of exposition were 9,3 and 4,5 mg/mL respectively. The LD50 of the extract, with intraperitoneal administration was 1205 mg/kg and by oral via not produce mortality in doses until 2000 mg/kg. At the doses of 8 and 32 mg/kg of extract, the repeated oral administration produced no toxic effects. Conclusions: In summary, this paper adds convincing evidences in support of innocuous of the aqueous extract of B.triquetrum. Altogether; these results represent another step towards the use of this natural product as phytotherapeutical agent.